Challenges with the Ultimate Energy Density with Li-ion Batteries. Issue 4 (May 2021) - Fang, Haoyu
Abstract: Challenges with the energy density with Li-ion batteries are reviewed. At present, Li-ion batteries are widely used in electronic equipment and electric vehicles, but the energy density is not high. It is important to find out the limitations of the energy density with Li-ion batteries. This essay will start the research with the structure of Li-ion batteries, study the chemistry behind Li-ion batteries and give a summary of the limitations of each battery part which affect energy density. In conclusion, it is the chemistry behind batteries that limits the energy density.